2019
DOI: 10.3389/fpls.2019.01537
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Spectral Reflectance Indices and Multivariate Modeling for Assessing Agronomic Parameters in Advanced Spring Wheat Lines Under Two Contrasting Irrigation Regimes

Abstract: The incorporation of nondestructive and cost-effective tools in genetic drought studies in combination with reliable indirect screening criteria that exhibit high heritability and genetic correlations will be critical for addressing the water deficit challenges of the agricultural sector under arid conditions and ensuring the success of genotype development. In this study, the proximal spectral reflectance data were exploited to assess three destructive agronomic parameters [dry weight (DW) and water content (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 78 publications
2
20
0
1
Order By: Relevance
“…Furthermore, plant water content affects chlorophyll content and canopy size. For this reason, previous findings indicated that bands in the visible region can be used indirectly to assess plant water status (Das et al, 2017;El-Hendawy et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, plant water content affects chlorophyll content and canopy size. For this reason, previous findings indicated that bands in the visible region can be used indirectly to assess plant water status (Das et al, 2017;El-Hendawy et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…However, moisture stress is one of the widespread abiotic factors limiting plant growth and productivity of major crops under irrigated agriculture. Additionally, abrupt climate change, high temperature and evaporation rates, and sparse and highly variable rainfall further exacerbate the drought-stress problems in irrigated agriculture, which poses a serious threat to future global food security [ 2 , 3 , 4 ]. Consequently, maximizing production per unit of irrigation water applied by shifting the irrigation strategies of crops from the paradigm of full irrigation to deficit irrigation practices is one plausible solution for addressing water shortage in irrigated agriculture [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, moisture stress directly affects plant water status, which can interfere with normal plant functions and can cause substantial changes in morphological and physiological traits. These effects subsequently translate into substantial changes in crop growth and development with significantly decreased leaf area, biomass accumulation, photosynthesis efficiency, stomatal conductance, transpiration rate, and chlorophyll content and ultimately significant losses in SY [ 4 , 7 , 14 , 15 , 16 ]. These reports indicate that the close association between plant water status and available soil water can be exploited to effectively manage irrigation scheduling that involves deciding how much and when irrigation water should be applied and how to simultaneously maximize yield and water use efficiency through accurate estimation and monitoring of the various morpho-physiological indicators [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, several types of SRI that include 2-3 wavelengths have been developed to assess the Chl content and biomass of plants. Most of these SRIs are based on specific wavelengths within the green (550 nm), red (660-670 nm), red-edge (680-750 nm), and NIR (750-870 nm) regions [24,26,[37][38][39][40][41]. These specific wavelengths have been incorporated in simple mathematical formulas to eliminate the sensitivity of these wavelengths to other factors that also influence the spectral reflectance but not the plant variables of interest [42].…”
Section: Introductionmentioning
confidence: 99%